2023
DOI: 10.1021/jacs.3c06233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nickel(I)–Bromide Complexes via Oxidation and Ligand Displacement: Evaluation of Ligand Effects on Speciation and Reactivity

Samuel H. Newman-Stonebraker,
T. Judah Raab,
Hootan Roshandel
et al.

Abstract: Nickel's +1 oxidation state has received much interest due to its varied and often enigmatic behavior in increasingly popular catalytic methods. In part, the lack of understanding about Ni I results from common synthetic strategies limiting the breadth of complexes that are accessible for mechanistic study and catalyst design. We report an oxidative approach using tribromide salts that allows for the generation of a well-defined precursor, [Ni I (COD)Br] 2 , as well as several new Ni I complexes. Included amon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 64 publications
(137 reference statements)
1
11
0
1
Order By: Relevance
“…Previous work from our group focusing on C–N cross-coupling supports the feasibility of (DalPhos)Ni 0/II catalytic intermediates, in keeping with studies from others regarding (bisphosphine)Ni cross-couplings (e.g., C–N, C–S, and C–C). While we have shown that under some circumstances it is possible to achieve productive C–N cross-coupling catalysis commencing from (DalPhos)Ni I species, , it is unclear if turnover commences directly from (DalPhos)Ni I in these scenarios or whether redox events (e.g., dis/comproportionation) precede productive catalysis. , …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous work from our group focusing on C–N cross-coupling supports the feasibility of (DalPhos)Ni 0/II catalytic intermediates, in keeping with studies from others regarding (bisphosphine)Ni cross-couplings (e.g., C–N, C–S, and C–C). While we have shown that under some circumstances it is possible to achieve productive C–N cross-coupling catalysis commencing from (DalPhos)Ni I species, , it is unclear if turnover commences directly from (DalPhos)Ni I in these scenarios or whether redox events (e.g., dis/comproportionation) precede productive catalysis. , …”
Section: Introductionmentioning
confidence: 79%
“…While we have shown that under some circumstances it is possible to achieve productive C−N cross-coupling catalysis commencing from (DalPhos)Ni I species, 17,21 it is unclear if turnover commences directly from (DalPhos)Ni I in these scenarios or whether redox events (e.g., dis/comproportionation) precede productive catalysis. 22,23 With the aim of taking the first steps toward establishing a better understanding of our newly developed C−O crosscoupling chemistry, we initiated a study comparing the catalytic abilities of (bisphosphine)Ni I and (bisphosphine)Ni II precatalysts [Figure 1; bisphosphine = DalPhos or 1,1′bis(diphenylphosphino)ferrocene (DPPF)], both to assess their practical utility and to gain preliminary information regarding the viability of Ni(0/II) versus Ni(I/III) cycles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dabei erwiesen sich niedrigkoordinierte Komplexe als überraschend unreaktiv. 21) Hartwig und Mitarbeiter:innen widmeten sich bei Kupfer der oxidativen Addition von Elektrophilen. Sie wiesen erstmals einen Additionsprozess nach, bei dem eine Organokupfer(III)spezies entsteht (Abbildung 8C).…”
Section: Nitrido- Phosphidound Imidokomplexeunclassified
“…The authors proposed that the inclusion of 1,5cyclooctadiene (L7, COD) results in (L7)Ni(I)X Ni-8 (X = I, Br), 69 the identity of which has been recently supported by the isolation of [(COD)Ni-Br] 2 and [(L7) 2 Ni][Al(ORF) 4 ] Ni-9 (ORF = OC(CF 3 ) 3 ). 70,71 Introduction to anionic ligand disproportionation In situ reduction by anionic ligand disproportionation has been a widely reported method to access Ni(0) and Ni(II) species from R-Ni(II)X organometallic complexes (R = allyl, aryl, alkyl) which then can react by comproportionation to afford Ni(I) complexes. Alternatively, such Ni(I) intermediates can be accessed via oxidative addition of an organic halide to Ni(0)L n given that after ligand disproportionation and reductive elimination, Ni(0) and Ni(II) species are generated in equimolar ratios.…”
Section: Conclusion For Copper Speciesmentioning
confidence: 99%